(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Aesthetically pleasing and structurally sound tower systems that can withstand high winds and earthquakes are in high demand because to the fast growth of the telecommunications industry. The effect of wind and seismic loads on the performance transition of 100-foot, 150-foot, and 200-foot Mono-Lattice towers is compared. The Mono-Lattice tower is a combination of lattice towers and monopole towers, which combines the advantages of small footprint and beautiful appearance of monopole tower with that of higher rigidity and load-bearing capacity of lattice tower. Conforming to the requirements of IS 1893 (Part 1):2016, TIA-222-H, & IS 875 (Part 3):2015, Non-linear P-Delta analysis and Finite Element Analysis (FEA) have been carried out in the software tnxTower. One of several structural criteria that were tested was the height of the tower. These included base shear, bending moment and maximum horizontal deflection. The results showed that the wind exposure of the Mono-Lattice tower is lower than that of the full lattice tower and the wind induced deflection & bending moments are less than those of the traditional monopole tower. The Mono-Lattice’s rigidity and serviceability improved at 100 ft height, having a deflection of only 0.536 in. in a wind. Additionally, compared to lattice and monopole towers, wind-induced bending moments was much lower, suggesting better structural efficiency and less need for foundations. The seismic base shear values were comparatively higher in the case of the Mono-Lattice tower making the foundation design considerations more critical. The general conclusions of the analysis will indicate that for medium to high rise telecom applications the Mono-Lattice layout will be the best combination of aesthetics, structural performance, wind rejections, and a low base cost.